2020
DOI: 10.1080/03014460.2020.1781250
|View full text |Cite
|
Sign up to set email alerts
|

Developmental fitness curves: assessing sprint acceleration relative to age and maturity status in elite junior tennis players

Abstract: Background: The influence of maturity-status on athletic performance is reasonably well-documented. Methodological and practical issues of assessment and lack of longitudinal data have impacted the success of various models. Aim: To develop age-and sex-specific developmental curves for sprint acceleration in elite youth tennis players and to address variation in performance relative to chronological and biological age. Subjects and methods: Measures of acceleration were available for 3120 elite youth tennis pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Specifically, the players' biological age was determined by comparing their %AH with the corresponding chronological age in a reference population. The age thus determined in the reference population was designated as the player's biological age [ 22 , 23 ]. Chronological age at the time of collection was calculated to the closest decimal for all players with birthdates.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the players' biological age was determined by comparing their %AH with the corresponding chronological age in a reference population. The age thus determined in the reference population was designated as the player's biological age [ 22 , 23 ]. Chronological age at the time of collection was calculated to the closest decimal for all players with birthdates.…”
Section: Methodsmentioning
confidence: 99%
“…The time needed to complete these distances was measured to the nearest 0.001 s using electronic timing gates (Witty Wireless Training Timer, Microgate, Bolzano, Italy). 25,26 In addition, the time needed to complete the 505 change of direction test was also determined to the nearest 0.001 s using the same electronic timing gates. The 505 change of direction test consisted of a 5 m sprint, followed by a 180° turn and a 5 m sprint back to the starting line.…”
Section: Methodsmentioning
confidence: 99%
“…The appropriate planning of a long-term training process requires the use of control tests to keep up with the evolution of athletes' morphological and physical characteristics in relation to their specific sport performance (Kuzuhara et al, 2018;Ryan et al, 2018;Myburgh et al, 2020). It was shown that the monitoring of players' attributes is particularly important during periods of accelerated biological development in order to control the adaption to training exposure, to reduce the injury risk, and, thereby, to enhance the coaching effectiveness process (Ryan et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%